The performance of the (U plus Th)/He thermochronology laboratory at UNESP Rio Claro, Brazil - Siqueira-Ribeiro, Maria C. [UNESP]; Marin, Danieli F. C. [UNESP]; Hackspacher, Peter C. [UNESP]; Stuart, Finlay M. (Acad Brasileira De Ciencias, 2019)
We have developed the first laboratory for (U-Th-Sm)/He thermochronology measurements in South America. Helium is measured using a high-sensitivity magnetic sector mass spectrometer (GVI-Helix-SFT) and a double focusing single collector inductively coupled plasma mass spectrometer (Thermo Scientific ELEMENT2) is used for U, Th and Sm determinations. Repeated analyses of fragments of Durango fluorapatite crystals yields an average age of 31.6 +/- 1.6 Ma (2 sigma) (n=62). This overlaps the long-term average of Durango fluorapatite measured in laboratories worldwide. The analysis of multiple single apatite crystals of a Precambrian basement sample from Serra do Mar, southeastern Brazil, yields an average He age (60.5 +/- 8.7 Ma; n=8) that overlaps that measured in the SUERC laboratory (59.6 +/- 3 Ma; n=3). This confirms that the UNESP laboratory is capable of routinely measuring the (U-Th-Sm)/He ages of single apatite crystals.
Keywords: (U-Th)/He dating; He calibration; Noble Gas; Serra do Mar AHe ages